Self-Testing of Vision in Age-Related Macula Degeneration: A Longitudinal Pilot Study Using a Smartphone-Based Rarebit Test - Christina Winther; Lars Frisén (Journal of Ophthalmology)
Purpose. There is a need for efficient self-tests of vision in patients with neovascular age-related macula degeneration. A new tablet/smartphone application aiming to meet this need is described and its performance is assessed in a longitudinal pilot study. Materials and Methods. The new MultiBit Test (MBT) employs segmented digits defined by rarebits, that is, receptive field-size bright dots briefly presented against a dark background. The number of rarebits per digit segment was varied in a cyclic fashion, in preset steps. There were no fixation demands. Twenty-eight patients with neovascular AMD of varying severity were monitored for an average of 30 weeks. Test scores were evaluated on an individual basis, by contrasting observed trends with the clinical status recorded at independently scheduled clinical examinations. Results. Serial plots of MBT results revealed gradual improvement after successful antineovascular treatment. Recurrences were signalled by gradual deteriorations of results. Test results remained stable during clinically stable time intervals. MBT results agreed well with clinical assessments whereas an acuity test performed at chance level. The MBT was well accepted by all subjects. Conclusions. The MBT appears to have a good potential for effective self-testing of vision in AMD and merits large-scale studies. Exploration of MBT performance with other forms of macula conditions may be worthwhile.